Time Series Machine Learning For Hospitalized Patient Monitoring: Addressing Missing Data, Missing Labels, And High False Alarm Rates - Rath, Preetish. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Computer Science.; Advisor: Michael Hughes.; Committee: Eric Miller, Donna Slonim, Joyce Ho, and Liping Liu.; Keyword: Artificial intelligence.